Effect of neuromuscular electrical stimulation on exercise capacity in patients with severe chronic obstructive pulmonary disease: A randomised controlled trial. (August 2022) - Péran, Loic; Beaumont, Marc; Le Ber, Catherine; Le Mevel, Patricia; Berriet, Anne Cécile; Nowak, Emmanuel; Consigny, Maëlys; Couturaud, Francis
Objective: To compare strengthening by neuromuscular electrical stimulation versus cycle ergometer training during a pulmonary rehabilitation program, in patients with severe to very severe chronic obstructive pulmonary disease. Design: A prospective randomized controlled study. Setting: Two inpatient pulmonary rehabilitation centers. Subjects: Patients with severe to very severe chronic obstructive pulmonary disease and multidimensional index to predict risk of death ≥5, were randomly assigned to receive neuromuscular electrical stimulation or cycle ergometer training during pulmonary rehabilitation. Main measures: The primary endpoint was the change in exercise capacity using 1-min sit-to-stand test Secondary endpoints were the changes in exercise capacity using 6-min walk test, quadriceps strength, quality of life and dyspnea. Results: 102 patients were included. After 3 weeks, 47 patients in the neuromuscular electrical stimulation group, and 45 in the cycle ergometer training group were able to be analyzed. No significant difference was seen in the evolution of exercise capacity using 1-min sit-to-stand test (3.3 ± 3.8 and 2.6 ± 4.1) and 6-min walk test (37.8 ± 58.4 and 33.1 ± 46.7), in the evolution of quadriceps strength and endurance (9.2 ± 12.9 and 6.6 ± 16.1; 9.0 ± 13.2 and 6.2 ± 17.0), in the evolution of quality of life (St George's Respiratory Questionnaire: −11.3 ± 11.7 and −8.1 ± 11.6; COPD Assessment Test: −5.7 ± 7.1 and −4.7 ± 7.0), or in the evolution of dyspnea using Dyspnea 12 (−5.5 ± 10.2 and −5.9 ± 8.5) except using modified medical research council scale (95% confidence interval: 0.48 [0.05; 0.91], p = 0.027). Conclusion: We found no significant difference between the two programs on exercise capacity, quadriceps strength and quality of life.